Year Round. Method of speech development and correction - Pavlova U.B; Khotyleva T.U (Moscow State University of Psychology and Education, 2016)
This methodological manual is created based on analysis of many years of experience of teachers working with children with developmental disorders. The manual is aimed at getting pre-school children or first graders with speech and communication difficulties leading to academic failure ready for school. Сontinued. Beginning in № 1 (46), 2015